Analisa Implementasi Load Balancing Round Robin dan Least Connection pada Web Server (Studi Kasus PT UCC) - Ekmawan Khoif (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2021)
Abstract The web server is used at PT UCC to manage and store various information so that its presence must always be there when accessed by its workers both in low and high traffic conditions. Load balancing can be used to overcome slow connections and there is more than 1 server. In this study the author aims to compare the load balancing algorithm round robin and least connection using the nginx web server. The research is implementing the nginx web server because it is known for its opensource nature and has a load balancer function. Due to resource limitations, the server is run on a virtual machine that looks like a physical server. Server testing using httperf tools using throughput and response time measurement parameters. Testing by giving a load via httperf with a rate value of 30, 60 and 120. The results of the load balancing test, namely the least connection algorithm has a better throughput value and response time value than round robin. At a given low connection rate, a single server still has good performance. When providing more connection rates, load balancing systems have better capabilities than single server. Keywords: Load balancing, Roundrobin, Least connection, Nginx, Httperf